Fault Analysis and Structural Improvement Design of Planetary Gear in Wind Turbine Gearbox - Yonghong Li (Jixie chuandong)
Focusing on planetary gear fault of traditional NGW type wind turbine gearbox， the fault analysis in the process of using is carried out， finding out why the planetary gear is damaged and an improved design of transmission structure for wind turbine gearbox is presented．The structure, design requirements, load sharing measures and performance characteristics of NW type planetary transmission with internal gear rotation adopted in the improved design are described. The operation practice shows that the improved design of wind power gearbox has the characteristics of high bearing capacity， low noise，high reliability， high transmission efficiency and good maintainability．